Frequencies of polymorphisms of the Rh, Kell, Kidd, Duffy and Diego systems of Santa Catarina, Southern Brazil - Costa, Daiane Cobianchi (Rev Bras Hematol Hemoter, 2016)
BACKGROUND: Red blood cell genes are highly polymorphic with the distribution of alleles varying between different populations and ethnic groups. The objective of this study was to investigate gene polymorphisms of blood groups in the state of Santa Catarina, Southern Brazil. METHODS: Three hundred and seventy-three unrelated blood donors and 31 transfusion-dependent patients were evaluated to investigate polymorphisms of the Rh, Kell, Duffy, Kidd, and Diego blood group systems in a population from the state of Santa Catarina. The subjects, from seven regions that comprise the blood-banking network of the state, were assessed between August 2011 and March 2014. The genotypes of the Rh, Kell, Duffy, Kidd, and Diego systems were determined using the restriction fragment length polymorphism-polymerase chain reaction and allele-specific polymerase chain reaction techniques. RESULTS: The genotype frequencies in this study were significantly different when populations from different regions of Santa Catarina were compared. Furthermore, there were also significant differences in the genetic frequencies compared to other Brazilian states. The genotype frequencies of the Kell and Kidd blood groups are similar to European populations from Naples, Italy and Zurich, Switzerland. CONCLUSION: This article reports for the first time the frequency of polymorphisms of blood group systems in blood donors from Santa Catarina, Southern Brazil.